[Membership certificate of the Operative Bricklayers' Society]
Reproduction of colour lithograph, membership certificate of the Operative Bricklayers' Society, symbols of the history and the different processes involved in bricklaying Reproduction from unknown date of membership certificate of the Operative Bricklayers' Society; original dates from 1895 PO-1563